Konsep Nasikh Mansukh Jalaluddin Al-Suyuti Dan Implikasi Metode Pengajarannya Di Perguruan Tinggi - Imam Masrur (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2018)
Ali ibn Abi Thalib said, a judge without nasikh-mansukh knowledge can make damages. Imams said, everyone forbidden interpret al-Qur'an before he knows nasikh-mansukh. But, many university students can't detail nasakh verses, many literatures don't detail it, and teaching process isn't appropriate. It causes they get misunderstanding in determining of Islmic law. To limit the discussion, this article will explore and analyze nasikh-mansukh concept of Jalaluddin al-Suyuti and the implication in teaching process. This article showed that Jalaluddin al Suyuti explores nasikh-mansukh concept completely until mapping nasakh verses. Mapping nasakh verses are main poin in understanding nasikh-mansukh. Without it, someone become misunderstanding in determining of Islamic law. Finally, this article concluded that concept nasikh-mansukh of Jalaluddin al-Suyuti can support teaching process how to understand nasikh-mansukh corectly toward university students.